2011
DOI: 10.4028/www.scientific.net/amr.250-253.3228
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of IAQ under Up-Suction Exhaust Hood in Commercial Kitchen

Abstract: For particular commercial kitchen, using CFD software to build model according to the actual operation condition uttermost, adopting the exhaust system of up-suction hood, the effect of exhaust airflow rate on working temperature,velocity,CO2 concentration at main site in commercial kitchen is studied. According to the common four calculation methods of airflow rate of exhaust hood, the simulation results shows 4.81 m3/s of exhaust system can realize eliminating harmful gas quickly and effectively, IAQ is good… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Dahua Jiang etal. [5][6]studied the effect of exhaust airflow rate and ventilation mode on working temperature,velocity, CO 2 concentration at main site in simulated commercial kitchen. The aim of this paper is to investigate the indoor air quality in commercial kitchen using CFD code and field test in order to probe the factor of IAQ under the condition of natural and mechanical exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…Dahua Jiang etal. [5][6]studied the effect of exhaust airflow rate and ventilation mode on working temperature,velocity, CO 2 concentration at main site in simulated commercial kitchen. The aim of this paper is to investigate the indoor air quality in commercial kitchen using CFD code and field test in order to probe the factor of IAQ under the condition of natural and mechanical exhaust.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that IAQ can be very poor in residences with indoor smoking [1-2] or cooking. Cooking [3][4] in a confined space is a major source of indoor particles [5][6]. At the same time, epidemiological studies have observed an elevated incidence of cancers among non-smoking women with long term exposure of cooking fumes [7][8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that temperature affects productivity. If the temperature in the space increases by 10°F (5.5°C) above the comfort level, the productivity may drop as much as 30% [2].Previous studies have shown that IAQ can be very poor in residences with indoor smoking of cooking [3][4][5][6]. Cooking in a confined space is a major source of indoor particles [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%